Anti‐ribosomal P protein antibodies in patients with systemic lupus erythematosus is associated with hyperferritinemia. (18th November 2021) - Arinuma, Yoshiyuki; Hirohata, Shunsei; Isayama, Takuya; Hasegawa, Yasuhiro; Muramatsu, Takumi; Kondo, Junichi; Kanayama, Yoshiro; Ino, Kazuma; Matsueda, Yu; Oku, Kenji; Yamaoka, Kunihiro
Abstract: Aim: Anti‐ribosomal P protein antibodies (anti‐ribo P) have been reported as one of the specific autoantibodies in patients with systemic lupus erythematosus (SLE) and has been demonstrated to bind and activate macrophages in vitro. Clinically, hyperferritinemia has been known to be a biomarker for macrophage activation. The aim of this study is to clarify the relationship of anti‐ribo P and clinical characteristics and biomarkers including serum ferritin in patients with SLE. Methods: Clinical parameters and laboratory data were measured in patients with active SLE (N = 127) in our university hospital. The risk factors affected by anti‐ribo P were retrospectively calculated by logistic regression analysis, and the correlation of anti‐ribo P and clinical factors was demonstrated. Results: Anti‐ribo P was significantly elevated in active SLE compared to non‐SLE diseases ( P  < .0001). Sensitivity and the specificity of anti‐ribo P in patients with SLE were 32.0% and 99.3%, respectively. Patients positive for anti‐ribo P had the highest risk for elevated serum ferritin (odds ratio: 8.432). Accordingly, anti‐ribo P positive patients had significantly elevated serum ferritin compared to negative patients ( P  = .024). A significant positive correlation was observed between the anti‐ribo P titer and the serum ferritin level ( r 2  = .07, t = 5.22, P  = .0081), but not serum interleukin (IL)‐6 in SLE patients. Conclusion: The presence of anti‐ribo P is a risk factor for higher ferritin levels that is independent of systemic inflammation regulated by IL‐6. We speculate that anti‐ribo P could be directly associated with macrophage activation leading to hyperferritinemia in patients with SLE.